The application of OpenAI Technology in Marketing Activities - A Systematic Literature Review - Joanna Wiśniewska; Sebastian Matysik (Journal of Modern Science)
Objectives This article aims to assess empirical research papers on the application of OpenAI technology in marketing activities, with the goal of organizing current knowledge in this domain. To achieve this objective, the following questions were addressed: 1. Is there scientific interest in the application of OpenAI technology in marketing activities, and is it extensively discussed in researching works ? 2. What kinds and directions of the empirical researching works on this problem have been taken so far ?